Pedagogical Conditions Of Development Of Legal Culture In Academic Lyceum Students - Toshkenboyev Navrozbek Kasimjan Qizi (Zien Journals, 2024)
This article presents opinions and comments on the pedagogical conditions for the development of legal culture among academic lyceum students
Keywords: Modern technology; interactive methods; legal culture; opportunities